(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Тhe article shows for the first time the methods of obtaining quinazolin4-thione in high yields. Quinazolin-4-one thiolation reactions were carried out in two ways, P2S5 and Lawesson’s reagent.